Analysis of the Impact of Capital Structure and Profitability on Financial Performance : JEL Classification: G32, G35, L25, M21, O16 - Kinayah, Siti Adila; Arifani; Bahri, Syamsul (Generasi Sains Indonesia, 2026)
This study is intended to analyze the effect of profitability and capital structure of PT Indofood Sukses Makmur Tbk for the 2015-2024 period. The capital structure was determined on the basis of total liabilities, profitability was indicated by the net profit and financial performance was determined by total revenue. The research method used in this study was quantitative associative method with secondary data in the form of financial statements audited for one year. The descriptive statistics, classical assumption tests, multiple linear regression analysis and hypothesis tests were used for data analysis, with IBM SPSS Statistics 30 software used. The results show that to a certain extent, capital structure and profitability have no significant impact on financial performance. However, at the same time both are playing an important role in the overall performance of the company in terms of revenue. The findings suggest that the synergy between financing strategy and the profitability of operations has a significant impact on corporate financial performance, which is more important than relying on individual financial metrics. The novelty of the study is using revenue as a proxy for financial performance and Indonesian food and beverage industry which has not been explored in corporate finance literature. The findings have theoretical implications for financial management studies and practical implications for the managers when introducing balanced financing and profitability strategies to ensure long-term sustainability and competitiveness of companies.